1999
DOI: 10.1038/sj.bjc.6690623
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-specific arginine vasopressin promoter activation in small-cell lung cancer

Abstract: Small-cell lung cancer (SCLC) can produce numerous mitogenic neuropeptides, which are not found in normal respiratory epithelium. Arginine vasopressin is detected in up to two-thirds of SCLC tumours whereas normal physiological expression is essentially restricted to the hypothalamus. This presents the opportunity to identify elements of the gene promoter which could be exploited for SCLC-specific targeting. A series of human vasopressin 5′ promoter fragments (1048 bp, 468 bp and 199 bp) were isolated and clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Overexpression of USF‐2 in NSCLC stimulates cell proliferation in vitro and we have previously shown that USF‐2 is transcriptionally active in transfected NCI‐H460, where it binds on gel‐shift analysis and switches on promoter‐driven reporter gene expression for both AVP 9 and CGRP 19. In agreement with these data, the highest endogenous USF‐2 expression was observed in Lu‐165 (Figure 1A), a SCLC cell line with very high constitutive expression of AVP 35. USF mutants did not stimulate proliferation in NCI‐H460, consistent with the lack of function associated with their loss of DNA binding or transcriptional activation domains 37 and their ability to reduce reporter gene activity dependent on the AVP promoter 23.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Overexpression of USF‐2 in NSCLC stimulates cell proliferation in vitro and we have previously shown that USF‐2 is transcriptionally active in transfected NCI‐H460, where it binds on gel‐shift analysis and switches on promoter‐driven reporter gene expression for both AVP 9 and CGRP 19. In agreement with these data, the highest endogenous USF‐2 expression was observed in Lu‐165 (Figure 1A), a SCLC cell line with very high constitutive expression of AVP 35. USF mutants did not stimulate proliferation in NCI‐H460, consistent with the lack of function associated with their loss of DNA binding or transcriptional activation domains 37 and their ability to reduce reporter gene activity dependent on the AVP promoter 23.…”
Section: Discussionsupporting
confidence: 82%
“…A pSG5 vector control (Stratagene) was used in transfections. 5 × 10 6 cells in 400 µl RPMI/10% BCS were transfected with 20 µg plasmid by electroporation, as previously described 35.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The promoters for arginine vasopressin and the cell surface antigen CD24 genes have been suggested, but have not yet been tested with therapeutic genes. 8,9 The neuron-specific enolase promoter has been tried for gene therapy for SCLC, but expression of a suicide gene from this promoter could not mediate cell death. 10 Both tumor expression and serum levels of the gastrin releasing peptide (GRP) has been used as a marker for SCLC.…”
Section: Introductionmentioning
confidence: 99%
“…4 In support of this, other investigators have recently shown that vasopressin gene expression by this tumor type could result from the presence of an aberrant suppressor protein that normally binds to the upstream coding region for the vasopressin gene. 5 Part of our demonstration of vasopressin gene expression involved immunohistochemistry performed with polyclonal antibodies recognizing different regions of the provasopressin molecule. 6 Antibodies directed against vasopressin or the linkage regions between vasopressin and neurophysin each reacted positively with all SCLC tumors examined, while antibodies against the glycopeptide moiety (VAG) at the C-terminal region of provasopressin reacted positively with approximately 84% of tumors.…”
mentioning
confidence: 99%